The Role of Astrocytes in Poststroke Rehabilitation - Ying Han; Li Huang; Jiaojiao Wu; Guiling Wan; Linhong Mo; Aixian Liu (Brain and Behavior)
ABSTRACT Introduction Ischemic stroke is a leading cause of death and chronic disability worldwide. Therapeutic options to reduce stroke‐related disability are still limited. Resident astrocytes are the most abundant glial cells in the brain and respond to the pathophysiological changes induced by ischemic stroke. Methods Comprehensive literature search and narrative review to summarize the current field of astrocytes in poststroke rehabilitation using the PubMed database. Results This review first presents that astrocyte activation is critical for scar formation, synaptogenesis, synaptic remodeling, inflammation limitation, and metabolic regulation. Next, we summarize the contributions of astrocytes to neural repair after stroke with a focus on their effects on exercise, transcranial magnetic stimulation (TMS), transcranial electrical stimulation (tES), music therapy, acupuncture, hyperbaric oxygen therapy (HBOT), and enriched environment (EE). Conclusions In this review, we comprehensively analyze the role and possible mechanisms of astrocytes in various rehabilitative treatments and suggest that targeting astrocytes may be an effective strategy for the development of innovative therapeutic strategies for ischemic stroke.